Integration Efforts in Agriculture - Beke Lisányi, Judit (Applied Studies in Agribusiness and Commerce, 2018)
The economic and political transition brought many challenges for the Hungarian agricultural sector. The break-up of large agricultural holdings had serious negative impacts on food production and on the export of agricultural products. Capital intensive profit-seeking intermediaries dominate the trading of agricultural goods that has injurious effects in terms of downward pressure on production prices and an increase in consumer prices. Cooperatives have a key role in effectively tackling the common challenges that small-scale producers have to face. More vertical integration along the food chain could contribute to providing rural employment and to an increase in living standards in rural areas. This study reviews the development, the specific features and the driving forces of modern cooperatives in Central Europe in general, and in Hungary in particular. The focus is on the integrator role of cooperatives and their future role in our globalised world. JEL Classification: Q10, Q13